The symphony of temperance in Republic 4: Musical imagery and practical models - Lynch, T (Brill, 2017)
This paper calls into question a long-lasting but ill-founded tenet of Platonic scholarship, namely that Plato was not interested in, or aware of, the technical implications of the musical concepts he employed in the dialogues. Conversely, I will show how Plato exploited the technical and practical features of the concept of symphōnía dià pasôn, and of choral singing more generally, to highlight the unique role played by temperance (sōphrosýnē) in the ideal city. More precisely I contend that Plato’s musical images, far from being decorative or purely metaphoric devices, enrich our understanding of this ethical notion precisely by means of their technical and performative implications, which were very familiar to the original readers of the Republic. Hence musical theory and practice, in addition to being central elements of the cultural context in which Plato’s reflections must be interpreted, represent also a repertoire of concepts that significantly informed his philosophical theories.